The Pepper Mitogen-Activated Protein Kinase CaMAPK7 Acts as a Positive Regulator in Response to Ralstonia solanacearum Infection - Shi, Lanping; Zhang, Kan; Xie, Linjing; Yang, Mingxing; Xie, Baixue; He, Shuilin; Liu, Zhiqin (Frontiers in Microbiology, 2021)
Mitogen-activated protein kinase (MAPK) pathways play a vital role in multiple plant processes, including growth, development, and stress signaling, but their involvement in response to Ralstonia solanacearum is poorly understood, particularly in pepper plants. Herein, CaMAPK7 was identified from the pepper genome and functionally analyzed. The accumulations of CaMAPK7 transcripts and promoter activities were both significantly induced in response to R. solanacearum strain FJC100301 infection, and exogenously applied phytohormones, including methyl jasmonate (MeJA), brassinolide (BR), salicylic acid (SA), and ethephon (ETN), were decreased by abscisic acid (ABA) treatment. Virus-induced gene silencing (VIGS) of CaMAPK7 significantly enhanced the susceptibility of pepper plants to infection by R. solanacearum and downregulated the defense-related marker genes, including CaDEF1, CaPO2, CaSAR82A, and CaWRKY40. In contrast, the ectopic overexpression of CaMAPK7 in transgenic tobacco enhanced resistance to R. solanacearum and upregulated the defense-associated marker genes, including NtHSR201, NtHSR203, NtPR4, PR1a/c, NtPR1b, NtCAT1, and NtACC. Furthermore, transient overexpression of CaMAPK7 in pepper leaves triggered intensive hypersensitive response (HR)-like cell death, H2O2 accumulation, and enriched CaWRKY40 at the promoters of its target genes and drove their transcript accumulations, including CaDEF1, CaPO2, and CaSAR82A. Taken together, these data indicate that R. solanacearum infection induced the expression of CaMAPK7, which indirectly modifies the binding of CaWRKY40 to its downstream targets, including CaDEF1, CaPO2, and CaSAR82A, ultimately leading to the activation of pepper immunity against R. solanacearum. The protein that responds to CaMAPK7 in pepper plants should be isolated in the future to build a signaling bridge between CaMAPK7 and CaWRKY40.